Deep Brain Stimulation for Refractory Obsessive-Compulsive Disorder: Towards an Individualized Approach - Senova, Suhan; Clair, Anne-Hélène; Palfi, Stéphane; Yelnik, Jérôme; Domenech, Philippe; Mallet, Luc (Frontiers in Psychiatry, 2019)
Obsessive-compulsive disorder (OCD) is a neuropsychiatric disorder featuring repetitive intrusive thoughts and behaviors associated with a significant handicap. Of patients, 20% are refractory to medication and cognitive behavioral therapy. Refractory OCD is associated with suicidal behavior and significant degradation of social and professional functioning, with high health costs. Deep brain stimulation (DBS) has been proposed as a reversible and controllable method to treat refractory patients, with meta-analyses showing 60% response rate following DBS, whatever the target: anterior limb of the internal capsule (ALIC), ventral capsule/ventral striatum (VC/VS), nucleus accumbens (NAcc), anteromedial subthalamic nucleus (amSTN), or inferior thalamic peduncle (ITP). But how do we choose the “best” target? Functional neuroimaging studies have shown that ALIC-DBS requires the modulation of the fiber tract within the ventral ALIC via the ventral striatum, bordering the bed nucleus of the stria terminalis and connecting the medial prefrontal cortex with the thalamus to be successful. VC/VS effective sites of stimulation were found within the VC and primarily connected to the medial orbitofrontal cortex (OFC) dorsomedial thalamus, amygdala, and the habenula. NAcc-DBS has been found to reduce OCD symptoms by decreasing excessive fronto-striatal connectivity between NAcc and the lateral and medial prefrontal cortex. The amSTN effective stimulation sites are located at the inferior medial border of the STN, primarily connected to lateral OFC, dorsal anterior cingulate, and dorsolateral prefrontal cortex. Finally, ITP-DBS recruits a bidirectional fiber pathway between the OFC and the thalamus. Thus, these functional connectivity studies show that the various DBS targets lie within the same diseased neural network. They share similar efficacy profiles on OCD symptoms as estimated on the Y-BOCS, the amSTN being the target supported by the strongest evidence in the literature. VC/VS-DBS, amSTN-DBS, and ALIC-DBS were also found to improve mood, behavioral adaptability and potentially both, respectively. Because OCD is such a heterogeneous disease with many different symptom dimensions, the ultimate aim should be to find the most appropriate DBS target for a given refractory patient. This quest will benefit from further investigation and understanding of the individual functional connectivity of OCD patients.